2018
DOI: 10.1021/acs.energyfuels.8b00596
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Structural Analysis of Silica Gel Fractions from Municipal Waste Pyrolysis Oils

Abstract: Hydrocarbon-rich pyrolysis oils produced from landfill waste and recycled plastics are potential sources for fuels and chemicals. It is well established that feedstock composition significantly affects pyrolysis oil composition and, hence, its potential uses. For example, plastics waste pyrolysis oils contain a high concentration of hydrocarbons, whereas biomass pyrolysis oils have high oxygen content. Previous studies have shown that the addition of plastics to a biomass feedstock increases the hydrocarbon co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Fourier transform ion cyclotron resonance (FTICR) mass spectrometers with a high magnetic field offer the best performances in terms of resolution, mass accuracy, and dynamic range. Over the past 20 years, it has been widely used to decipher ultracomplex mixtures. In the case of plastic pyrolysis oil, two studies using FTICR-MS reported their molecular characterization with atmospheric pressure photoionization (APPI). This enabled the characterization of hydrocarbon compounds and a part of oxygenated compounds defined as alcohols. , However, as stated before, the molecular characterization of other heteroatom-containing species such as nitrogen species is also important in order to anticipate their impact on the refining process. Depending on the ionization method, different ionization selectivities can be obtained in order to detect specific families of compounds. Electrospray ionization (ESI) is known to be selective of basic and acidic compounds using the positive and negative ion modes, respectively, while APPI and atmospheric pressure chemical ionization (APCI) are less selective and allow for the detection of low-polarity species. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourier transform ion cyclotron resonance (FTICR) mass spectrometers with a high magnetic field offer the best performances in terms of resolution, mass accuracy, and dynamic range. Over the past 20 years, it has been widely used to decipher ultracomplex mixtures. In the case of plastic pyrolysis oil, two studies using FTICR-MS reported their molecular characterization with atmospheric pressure photoionization (APPI). This enabled the characterization of hydrocarbon compounds and a part of oxygenated compounds defined as alcohols. , However, as stated before, the molecular characterization of other heteroatom-containing species such as nitrogen species is also important in order to anticipate their impact on the refining process. Depending on the ionization method, different ionization selectivities can be obtained in order to detect specific families of compounds. Electrospray ionization (ESI) is known to be selective of basic and acidic compounds using the positive and negative ion modes, respectively, while APPI and atmospheric pressure chemical ionization (APCI) are less selective and allow for the detection of low-polarity species. , …”
Section: Introductionmentioning
confidence: 99%
“…This enabled the characterization of hydrocarbon compounds and a part of oxygenated compounds defined as alcohols. 39,40 However, as stated before, the molecular characterization of other heteroatom-containing species such as nitrogen species is also important in order to anticipate their impact on the refining process. 41−43 Depending on the ionization method, different ionization selectivities can be obtained in order to detect specific families of compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The exciting principle behind twodimensional GC Â GC TOFMS is the separation of mixtures by the polarity of species compared to one-dimensional GC-MS separation based on the compounds' boiling point. [28][29][30]36 There are very few studies in the literature regarding the analysis of tire oil fractions using this advanced chromatographic technique. Ngxangxa reported that TPO is a complex mixture of C 6 -C 24 compounds, including paraffins, terpenes, monocyclic and PAHs, heterocyclic compounds, etc.…”
Section: Two Dimensional Gas Chromatography Time-of-ight Mass Spectrmentioning
confidence: 99%
“…Each was previously characterized using different analytical methods such as gas chromatography (GC), 21 , 23 26 infrared spectroscopy (IR), 27 nuclear magnetic resonance (NMR), 19 and mass spectrometry (MS). 12 , 16 , 25 Because pyrolysis oil is of particular interest for the recovery of monomers, the material chosen in this study is a pyrolysis oil produced from real municipal wastes made up of different plastic types. Owing to the high molecular complexity of such samples, the necessity of using very-high-resolution mass spectrometry such as Fourier transform ion cyclotron resonance (FTICR) to characterize plastic oils has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high molecular complexity of such samples, the necessity of using very-high-resolution mass spectrometry such as Fourier transform ion cyclotron resonance (FTICR) to characterize plastic oils has been demonstrated. 12 , 25 , 28 Specifically, in a previous study, the presence of nitrogen-containing species in the plastic pyrolysis oil was highlighted by electrospray ionization (ESI). 29 Nitrogen-containing species form due to the presence of antioxidant additives such as hindered amine light stabilizers (HALS) and nitrogen-containing polymers such as polyamides in the plastic waste.…”
Section: Introductionmentioning
confidence: 99%